Plant derived exosome- like Nanovesicles: an updated overview - D. Subha; K. Harshnii; K.G. Madhikiruba; M. Nandhini; K.S. Tamilselvi (Plant Nano Biology, 2023)
abstract: Exosomes are nanovesicles in the size range of 30–150 nm, produced by mammalian and plant cells. They have the lipid bilayer enclosing a unique mix of biologically active components including proteins, nucleic acids, metabolites and lipids, that depend on their source of origin. The plant derived nanovesicles are gaining considerable research attention due to their ability to be absorbed from the dietary sources. Their bioactive components impart many therapeutic properties to them such as anti-tumorigenic, anti-oxidative, anti-inflammatory, hepatoprotective effects and tissue regeneration. The possibilities of using plant derived exosomes for drug delivery is also promising. This review focusses on the biogenesis and biological nature of exosomes derived from plants and describes their various inherent therapeutic properties. It sheds light on the recently developed methods to study them. The existing challenges in the exosomal research as well as the future prospective are highlighted. Overall, it is an update on the advancements on the research in plant exosomes which can provide a replacement for toxic synthetic drugs and possibilities for disease therapy.